2023
DOI: 10.32792/utq/utjsci/v10i1.1040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid disorders in Nasiriya City, Iraq

Hind Mousa,
Ammani Zoori

Abstract: Abstract—. Thyroid disorders are the second biggestendocrine problem in society after diabetes.Environmental and genetic factors lead to thedevelopment of thyroid disorders. So this study designedto determine the prevalence of thyroid disorders inNasiriya city . One hundred-twenty subjects for bothgenders involved in this study , 80 of whom werepatients, and 40 of healthy people. A blood sample andpersonal information was collected from all . The levelsof thyroid hormones was estimate by Cobas e411 ElecteoChem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This study also found hypothyroidism to be more common in women aged 30 to 45 years, further emphasizing the gender and age-related variations in thyroid dysfunction rates within the Indian population [ 22 , 23 ]. Similarly, in a recent cross-sectional study conducted in Iraqi Kurdistan, primary hypothyroidism was significantly more prevalent in women compared to men, with a relative risk of 8-9 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also found hypothyroidism to be more common in women aged 30 to 45 years, further emphasizing the gender and age-related variations in thyroid dysfunction rates within the Indian population [ 22 , 23 ]. Similarly, in a recent cross-sectional study conducted in Iraqi Kurdistan, primary hypothyroidism was significantly more prevalent in women compared to men, with a relative risk of 8-9 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%